The Future of Catholic Theological Ethics - Anna Abram (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
'The Future of Catholic Theological Ethics' undertakes a search for new ways of making Catholic theological ethics relevant. It engages with a ground-breaking publication 'Reframing Catholic Theological Ethics' (Oxford University Press, 2016) by Joseph Selling, Emeritus Professor of Moral Theology, Catholic University Leuven. Selling opens the volume with a summary of the approach he developed in the above work. The papers presented here cover several major themes that, traditionally, Catholic theological ethics have considered but, according to the authors of the papers, need revisiting. Amongst these themes are: conscience, virtue, natural law, authority, ecumenism, the human person and the theology of theological ethics. The writers represent a variety of approaches, geographical locations and while most of them are Roman Catholic, there is an imbedded ecumenism and interreligious and inter-cultural slant in several discussions. The authors agree that Catholic theological ethics, in order to be relevant, it needs to become more context-sensitive, ecumenical, practice-based, experience-oriented, continuously discerning, pedagogically wide-ranging and theologically articulate. It must be unceasingly willing to review and renew its method as well as revisit its key concepts. It must neither dismiss its long tradition nor stick to its single interpretation.